Competition Enhances the Effectiveness and Motivation of Attention Rehabilitation After Stroke. A Randomized Controlled Trial - Navarro, María Dolores; Llorens, Roberto; Borrego, Adrián; Alcañiz, Mariano; Noé, Enrique; Ferri, Joan (Frontiers in Human Neuroscience, 2020)
Attention deficits are among the most common cognitive impairments observed after experiencing stroke. However, a very limited number of studies have investigated the effectiveness of interventions that specifically focus on the rehabilitation of attention deficits among subjects with impaired attention. Although several interventions including subjects without attentional impairments have included the use of computerized tools in rehabilitation programs to provide dynamic stimuli, real-time performance feedback, and motivating tasks, existing studies have not exploited the potential benefits of multi-user interactions to the rehabilitation of attention deficits. Group-based and competitive interventions have been reported to be more enjoyable and motivating, depending on individual traits, and may potentially be more demanding, which may increase their effectiveness. This study investigated the effectiveness and motivating abilities of an intervention specifically designed to address attention deficits. This intervention combined paper-and-pencil tasks and interactive, computerized, multi-touch exercises, which were administered, either non-competitively or competitively, to a group of 43 individuals with chronic stroke. The mediating effects of competitiveness were evaluated for both intervention effectiveness and motivation. Participants were randomly sorted into two groups and underwent 20 one-hour group-based sessions, during which they either worked individually or competed with peers, according to their group allocation. Participants were assessed before and after the intervention, using the Conners’ Continuous Performance Test, the d2 Test of Attention, the Color Trail Test, the Digit Span Test, and the Spatial Span Test. The competitiveness and subjective experiences of the participants after the intervention were investigated with the Revised Competitiveness Index and the Intrinsic Motivation Inventory, respectively. The results showed that participants who competed demonstrated significantly greater improvements in all cognitive abilities, except for divided attention, and reported greater enjoyment than their non-competitive peers. Both groups reported comparable levels of perceived competence, pressure, and usefulness. Interestingly, the competitiveness of the participants did not alter either the effectiveness or the subjective experience of the intervention. These findings suggest that competition might enhance the effectiveness and enjoyment of rehabilitation interventions designed to address attention deficits in individuals post-stroke, regardless of their level of competitiveness and without having a negative effect on their perceived pressure and competence.